2017
DOI: 10.3892/mco.2017.1318
|View full text |Cite
|
Sign up to set email alerts
|

Expression of programmed death ligand-1 predicts poor outcome in nasopharyngeal carcinoma

Abstract: Abstract. Programmed death ligand-1 (PD-L1) is a potentially important tumor immunotherapy target. However, whether PD-L1 expression is associated with survival in nasopharyngeal carcinoma (NPC) remains controversial. The aim of the present study was to investigate the association between PD-L1 expression and prognosis in NPC. The expression of PD-L1 was assessed in tumor specimens from 120 patients with NPC using immunohistochemistry. Staining was evaluated using the H-score method. The associations between P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
4
33
3
Order By: Relevance
“…Previous studies on the clinical significance of PD-L1 expression in NPC showed conflicting results [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The EBV status could influence their results, since all previous studies either worked on a mixed cohort of EBV-positive and EBV-negative cases or did not show results of EBV-encoded small RNAs (EBER) in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the clinical significance of PD-L1 expression in NPC showed conflicting results [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The EBV status could influence their results, since all previous studies either worked on a mixed cohort of EBV-positive and EBV-negative cases or did not show results of EBV-encoded small RNAs (EBER) in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a monoclonal anti-PD-1 antibody pembrolizumab has been shown to exhibit anti-tumor effects in patients with PD-L1-positive NPC [ 18 ]. However, the clinical significance of PD-L1 expression in NPC remains controversial, with previous studies showing conflicting conclusions [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In the present study, we evaluated the clinical significance of PD-L1 expression on tumor cells (TCs) and immune cells (ICs) in 208 NPC patients who underwent radiation-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Frigola et al (17) indicated that the expression of PD-L1 was associated with the tumor stage and prognosis in patients with renal cell carcinoma. Li et al (23) reported that high tumor expression of PD-L1 was associated with significantly poorer OS and DFS. Compared with other types of head and neck tumor, NPC has a higher risk of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that NF‐κB activation contribute to LMP‐1 mediated induction of PD‐L1 in NPC cells and natural killer/T‐cell lymphoma (Bi et al, ; Fang et al, ) (Figure ). However, the relationship between PD‐L1 expression and NPC clinical outcomes is remain controversial (Li, Ding, et al, ; Zhu et al, ). A latest clinical trial result revealed that Keytruda (Pembrolizumab) exert antitumor activity with a manageable safety in recurrent or metastatic nasopharyngeal carcinoma (RM‐NPC) patients with PD‐L1 expression (Hsu et al, ).…”
Section: The Pd‐1:pd‐l1 Immune Checkpointmentioning
confidence: 99%